Septic Shock Alters Mitochondrial Respiration of Lymphoid Cell-Lines and Human Peripheral Blood Mononuclear Cells: The Role of Plasma. Issue 1 (January 2019) - Clere-Jehl, Raphael; Helms, Julie; Kassem, Mohamad; Le Borgne, Pierrick; Delabranche, Xavier; Charles, Anne-Laure; Geny, Bernard; Meziani, Ferhat; Bilbault, Pascal
ABSTRACT: Introduction: In septic shock patients, postseptic immunosuppression state after the systemic inflammatory response syndrome is responsible for nosocomial infections, with subsequent increased mortality. The aim of the present study was to assess the underlying cellular mechanisms of the postseptic immunosuppression state, by investigating mitochondrial functions of peripheral blood mononuclear cells (PBMCs) from septic shock patients over 7 days. Materials and methods: Eighteen patients admitted to a French intensive care unit for septic shock were included. At days 1 and 7, PBMCs were isolated by Ficoll density gradient centrifugation. Mitochondrial respiration of intact septic PBMCs was assessed versus control group PBMCs, by measuring O2 consumption in plasma, using high-resolution respirometry. Mitochondrial respiration was then compared between septic plasmas and control plasmas for control PBMCs, septic PBMCs, and lymphoid cell-line (CEM). To investigate the role of plasma, we measured several plasma cytokines, among them High-Mobility Group Box 1 (HMGB1), by enzyme-linked immunosorbent assays. Results: Basal O2 consumption of septic shock PBMCs was of 8.27 ± 3.39 and 10.48 ± 3.99 pmol/s/10 6 cells at days 1 and 7, respectively, significantly higher than in control PBMCs (5.37 ± 1.46 pmol/s/10 6 cells, P < 0.05). Septic patient PBMCs showed a lower response to oligomycin, suggesting a reduced ATP-synthase activity, as well as an increased response to carbonyl cyanide 4-(trifluoromethoxy)phenylhydrazone (FCCP) suggesting an increased mitochondrial respiratory capacity. At 6 h, septic plasmas showed a decreased O2 consumption of CEM (4.73 ± 1.46 vs. 6.58 ± 1.53, P < 0.05) as well as in control group PBMCs (1.76 ± 0.36 vs. 2.70 ± 0.42, P < 0.05), and triggered a decreased ATP-synthase activity but an increased response to FCCP. These differences are not explained by different cell survival. High HMGB1 levels were significantly associated with reduced PBMCs mitochondrial respiration. Conclusions: Septic plasma impairs mitochondrial respiration in immune cells, with a possible role of the proinflammatory protein HMGB1, leading to a subsequent compensation, probably by enzymatic activation. This compensation result is an improvement of global mitochondrial respiratory capacity, but without restoring ATP-synthase activity. Abstract : Supplemental Digital Content is available in the text